2013
DOI: 10.1152/ajpgi.00491.2012
|View full text |Cite
|
Sign up to set email alerts
|

The peptide transporter PEPT1 is expressed in distal colon in rodents and humans and contributes to water absorption

Abstract: The peptide transporter PEPT1, expressed in the brush border membrane of enterocytes, mediates the uptake of di- and tripeptides from luminal protein digestion in the small intestine. PEPT1 was proposed not to be expressed in normal colonic mucosa but may become detectable in inflammatory states such as Crohn's disease or ulcerative colitis. We reassessed colonic expression of PEPT1 by performing a systematic analysis of PEPT1 mRNA and protein levels in healthy colonic tissues in mice, rats, and humans. Immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 38 publications
(46 reference statements)
2
39
0
Order By: Relevance
“…However, expression of PepT1 in the large intestine is controversial and may be species- and/or region-dependent [43]. In the current study, cefadroxil permeability was high in the duodenum, jejunum and ileum in both wildtype and huPepT1 mice, agreeing with the protein expression pattern of PepT1 in these two genotypes [5,12].…”
Section: Discussionsupporting
confidence: 83%
“…However, expression of PepT1 in the large intestine is controversial and may be species- and/or region-dependent [43]. In the current study, cefadroxil permeability was high in the duodenum, jejunum and ileum in both wildtype and huPepT1 mice, agreeing with the protein expression pattern of PepT1 in these two genotypes [5,12].…”
Section: Discussionsupporting
confidence: 83%
“…In support of this, absorption of radiolabeled PepT1 substrate, Gly-Sar peptide, was higher in the everted sacs from the murine distal colon than in the proximal segment, and higher than in PepT1 −/− mice. Moreover, the study also suggested an involvement of PepT1 in the colonic electrolyte and water transport in mice (48). The mechanism for increased water content in the stools of PepT1 −/− mice, as well as the basis for these controversial findings remains to be elucidated.…”
Section: Epithelial Transport Of Macronutrients In Ibdmentioning
confidence: 89%
“…Interestingly, the concept of inducible expression of PepT1 in the colon has been recently challenged in a report by Wuensch et al (48). This group demonstrated detectable apical expression of PEPT1 in the distal (but not proximal) colon in three strains of mice, in rats, and in humans under non-inflammatory conditions.…”
Section: Epithelial Transport Of Macronutrients In Ibdmentioning
confidence: 99%
“…By contrast, di-and tripeptides absorption depends exclusively on the intestinal H ϩ /peptide cotransporter-1 Slc15a1 (PEPT1). This transporter is highly expressed in the small intestine (duodenum, jejunum, and ileum) and also expressed in the distal part of the colon (61). PEPT1 is a high-capacity transporter since it is responsible for the absorption of 70% of dietary nitrogen supplied to the body.…”
mentioning
confidence: 99%